2014
DOI: 10.1177/0146167214551153
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming the Barrier of Narrative Adherence in Conflicts Through Awareness of the Psychological Bias of Naïve Realism

Abstract: One significant socio-psychological barrier for peaceful resolution of conflicts is each party's adherence to its own collective narrative. We hypothesized that raising awareness to the psychological bias of naïve realism and its identification in oneself would provide a path to overcoming this barrier, thus increasing openness to the adversary's narrative. We conducted three experimental studies in the context of the Israeli-Palestinian conflict. Studies 1 and 2, conducted among Jewish Israelis and Palestinia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
47
1
5

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(65 citation statements)
references
References 46 publications
(50 reference statements)
4
47
1
5
Order By: Relevance
“…This cannot be done by replacing a master narrative with another well-intentioned simplistic peace narrative or with the strategic use of essentialist and reified forms of identity and social representations of the past. What is needed is a history teaching that is epistemologically more advanced compared to collective memory or the teaching of history as heritage (lowenthal 1996;Makriyianni and Psaltis 2007), not only because more de-centred and multi-perspective forms of knowledge as we know from the genetic epistemology of Jean Piaget are more advanced forms of knowing compared to monoperspective accounts (see Makriyianni and Psaltis 2007) but also because developing the historical literacy, and their epistemological stance of history (Nasie et al 2014), allows them to take an informed, critical and reflective stance on diverse representations and interpretations of the past. The main message of this volume is that we need to move from the disciplinary to the interdisciplinary teaching of history.…”
Section: Conflict Transformation Conflict Resolution and Reconciliatmentioning
confidence: 99%
“…This cannot be done by replacing a master narrative with another well-intentioned simplistic peace narrative or with the strategic use of essentialist and reified forms of identity and social representations of the past. What is needed is a history teaching that is epistemologically more advanced compared to collective memory or the teaching of history as heritage (lowenthal 1996;Makriyianni and Psaltis 2007), not only because more de-centred and multi-perspective forms of knowledge as we know from the genetic epistemology of Jean Piaget are more advanced forms of knowing compared to monoperspective accounts (see Makriyianni and Psaltis 2007) but also because developing the historical literacy, and their epistemological stance of history (Nasie et al 2014), allows them to take an informed, critical and reflective stance on diverse representations and interpretations of the past. The main message of this volume is that we need to move from the disciplinary to the interdisciplinary teaching of history.…”
Section: Conflict Transformation Conflict Resolution and Reconciliatmentioning
confidence: 99%
“…The cognitive factor , which includes long-standing beliefs, may appear most resistance to change, but in a recent series of studies, Nasie and colleagues have shown that merely raising people's awareness to a common psychological bias may facilitate unfreezing of long-standing beliefs. When both Jewish and Palestinian citizens of Israel were made aware of naïve realism, a cognitive bias limiting their ability to recognize beliefs other than their own as valid, they were more open to new information presenting the adversary's beliefs on the confl ict, even though this information was entirely incongruent with their own long-held beliefs (Nasie et al 2013 ).…”
Section: Unfreezing Processmentioning
confidence: 99%
“…In Israel, for example, a series of anti-conflict interventions being developed under the leadership of psychologist Eran Halperin at the Interdisciplinary Center Herzliya in Israel have proved effective in making people more open to seeing things from the other side's point of view [3][4][5] .…”
Section: State Of Mindmentioning
confidence: 99%